Corruption and the Desire to Leave Quasi-Experimental Evidence on Corruption as a Driver of Emigration Intentions - Daniel Auer; Friederike Römer; Jasper Tjaden (IZA Journal of Development and Migration, 2020)
Whether and to what extent corruption drives emigration has received growing attention in the literature in recent years, yet the nature of the relationship remains unclear. To test causal claims, we rely on representative global survey data of more than 280,000 respondents across 67 countries from 2010 to 2014. We use two different measures of emigration intentions and individual, as well as country-level measures of corruption, and propose to instrument the endogenous presence of corruption in a country with the prevalence of cashless transactions in the economy to correct for potential estimation bias. We find robust support for the hypothesis that corruption increases emigration intentions across countries. The effect, however, is likely to be underestimated in conventional models that do not account for endogeneity. The results highlight the need to look beyond purely economic, social, security-related, and environmental drivers when assessing the root causes of migration.
Keywords: D73; F22; O12; O15; 330; corruption; governance; migration; push factor; emigration intention